Isquemia de membro superior: um desafio diagnóstico e terapêutico - relato de caso - França, Bruna Araújo; Monteiro, Anamaria Martins; Carvalho, Rebeca de Sousa; Vasconcelos, Jersica Caires; da Silva, Sílvio Alves; da Costa Júnior, Antônio Fagundes (Revista de Patologia do Tocantins, 2017)
Ao contrário da isquemia dos membros inferiores, evento frequente, cuja principal causa é a doença aterosclerótica, a isquemia dos membros superiores é rara e decorre principalmente da doença tromboembólica associada a fibrilação atrial. O presente relato de caso refere-se a uma paciente jovem (46 anos), hipertensa e tabagista com claudicação de membro superior esquerdo, cuja arteriografia evidenciou trombo em bifurcação da artéria braquial. A abordagem inicial baseou-se em anticoagulação, antiagregação plaquetária, analgesia, aquecimento do membro e controle pressórico. A história clínica e o exame físico em conjunto com eletrocardiograma e ecocardiograma normais, bem como sorologias negativas para pesquisa de síndrome do anticorpo antifosfolípide, biópsia arterial e angiorressonância do membro acometido sem evidências de vasculite permitiram a exclusão dos principais diagnósticos diferenciais aventados para o quadro. O diagnóstico etiológico estabelecido foi, então, Doença Arterial Obstrutiva Periférica por aterosclerose. Foi mantido o tratamento conservador porém, sem melhora clínica. No sétimo dia de internação, então, foi realizada tromboembolectomia com cateter de Fogarty número 3. A paciente, no segundo pós-operatório, evoluiu com reobstrução da artéria braquial. A equipe optou por tratamento conservador, alcançando melhora importante, todavia parcial, dos sintomas, após 14 dias de internação hospitalar. Recebeu alta para acompanhamento ambulatorial em uso de cilostazol, AAS e rivaroxabano, além de orientações sobre interrupção do tabagismo, dieta adequada e controle pressórico. A paciente apresentou sintomas remanescentes leves após um mês de seguimento. Palavras-chave: Membro superior. Doença arterial periférica. Aterosclerose. Isquemia. ABSTRACT Unlike the lower limb ischemia, a frequent occurrence, whose main cause is the aterosclerotic disease, upper limb ischemia is a rare condition and often stems from the combination of tromboembolic disease and atrial fibrilation. This report refers to a 46 year old female patient, with a history of hypertension and tobacco use, presenting left upper limb claudication, whose arteriography pointed to a clot on the brachial artery bifurcation. The initial approach consisted on anticoagulation and antiplatetet therapy, analgesia, warming-up the limb and blood pressure control. The conjunction of anamnesis, physical examination, unaltered results of the electrocardiogram and echocargiogram, negative sorologies for antiphospholipid antibody syndrome and the abscense of vasculitis’ signs in the arterial biopsy and angioresonance allowed the exclusion of most initial differential diagnosis. Therefore, the etiological diagnosis established was Peripheral Obstructive Artery Disease secondary to Atherosclerosis. Conservative treatment was sustained, but no subsequent clinical improvement was observed. After one week of hospitalization, a thromboembolectomy was performed using a number 3 Fogarty catheter, the patient evolved with brachial artery re-obstruction 2 days later. The medical team suspended invasive methods and kept the conservative treatment, which achieved important, yet partial, clinical progress. The patient was discharged from the hospital after 14 days with an outpatient prescription for cilostazol, acetylsalicylic acid, rivoraxaban and behavioral recommendations. One month later, in the outpatient follow-up, the patient presented mild remnant symptoms. Keywords: Upper extremity. Peripheral arterial disease. Atherosclerosis. Ischemia. ABSTRACT Unlike the lower limb ischemia, a frequent occurrence, whose main cause is the aterosclerotic disease, upper limb ischemia is a rare condition and often stems from the combination of tromboembolic disease and atrial fibrilation. This report refers to a 46 year old female patient, with a history of hypertension and tobacco use, presenting left upper limb claudication, whose arteriography pointed to a clot on the brachial artery bifurcation. The initial approach consisted on anticoagulation and antiplatetet therapy, analgesia, warming-up the limb and blood pressure control. The conjunction of anamnesis, physical examination, unaltered results of the electrocardiogram and echocargiogram, negative sorologies for antiphospholipid antibody syndrome and the abscense of vasculitis’ signs in the arterial biopsy and angioresonance allowed the exclusion of most initial differential diagnosis. Therefore, the etiological diagnosis established was Peripheral Obstructive Artery Disease secondary to Atherosclerosis. Conservative treatment was sustained, but no subsequent clinical improvement was observed. After one week of hospitalization, a thromboembolectomy was performed using a number 3 Fogarty catheter, the patient evolved with brachial artery re-obstruction 2 days later. The medical team suspended invasive methods and kept the conservative treatment, which achieved important, yet partial, clinical progress. The patient was discharged from the hospital after 14 days with an outpatient prescription for cilostazol, acetylsalicylic acid, rivoraxaban and behavioral recommendations. One month later, in the outpatient follow-up, the patient presented mild remnant symptoms. Keywords: Upper extremity. Peripheral arterial disease. Atherosclerosis. Ischemia.